Narrative enquiry and teacher’s education: change possibilities and the construction of teacher’s identity (Praxis Educativa, 2015)
Educational Research has a long tradition which presents multiple perspective and lines of enquiry. Within them, enquiries regarding Teachers´Education comprise a broad range of research leads. Current tendencies, such as narrative enquiry, constitute a strong trend dealing with narratives and teachers´ life stories. This article proposes a brief approach to the main qualitative research lines about teachers´ education, in order to explore the origins and tendencies brought about by narrative enquiry. It also explores its contribution as a tool for Teachers´ Education. Finally, we explore future trails already emerging in this field as a result of the ichness presented in the narratives produced in this research framework.
Keywords: educational research; teachers’ education; narrative enquiry; narrative pedagogy; new trends